2011
DOI: 10.1002/j.1681-4835.2011.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

The “I” Between G and C: E‐Government Intermediaries in Developing Countries

Abstract: While there has been a rapid growth in e-Government initiatives in developing countries, whether it has led to providing effective government services to the citizens has remained a question of concern. Evidence suggests that this objective is far from being met. The main hurdle has been that an overwhelming part of the citizens in these countries do not have the capability to either access government information physically or to use it effectively even when they can access it. In this paper, the conjecture is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Development work does not end upon the launch of an e‐government service (Bertot & Jaeger, ); it is continuous. As we investigate qualities of e‐government services in an LDC, it is important to recognize the dominant use of intermediaries; they intervene between the government and citizens to support citizens who cannot access or use information and services (Sein, ). Service providers welcomed the idea of getting users' feedback.…”
Section: Resultsmentioning
confidence: 99%
“…Development work does not end upon the launch of an e‐government service (Bertot & Jaeger, ); it is continuous. As we investigate qualities of e‐government services in an LDC, it is important to recognize the dominant use of intermediaries; they intervene between the government and citizens to support citizens who cannot access or use information and services (Sein, ). Service providers welcomed the idea of getting users' feedback.…”
Section: Resultsmentioning
confidence: 99%
“…However, organised intermediary functions have, to a large degree, been neglected and must be heavily emphasised, to develop telecentres into important actors in the distribution of e‐government and in development in general. Sein () has shown that intermediaries can play an important role in PIAP use in general and in e‐government use in particular, and in our opinion, the public sector has to take responsibility also for the demand side. This can be done through a public/private partnership with these potential intermediaries.…”
Section: Conclusion and Recommendationsmentioning
confidence: 93%
“…Our conceptualization is based on our own research work and on the few topologies that exist in the e-government literature (Sein, 2011;Sorrentino & Niehaves, 2010). We also draw upon research that has explicitly delved into the roles of Intermediaries (Al-Sobhi et al, 2010;OECD, 2010).…”
Section: Conceptualizing the Intermediary Entitymentioning
confidence: 99%
“…However, with a few notable exceptions, their involvement directly in the interaction process has received less explicit attention. Among the exceptions have been terming these third parties as intermediaries (Heeks, 2002), examining their roles in mediation (Beck, Madon, & Sahay, 2004;Madon & Sahay, 2002) and categorizing the different types of intermediaries in the specific context of e-government (Al-Sobhi, Weerakkody, & Kamal, 2010;Sein, 2011;Sorrentino & Niehaves, 2010). What is lacking is a systematic conceptualization of their characteristics, roles and form of intermediation in the wider context of ICT for development in general.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation